Silicon-containing material with VOC (volatile organic compound) adsorption function as well as preparation method and application of silicon-containing material
The multi-stage pore structure silicon-containing material prepared by hydrothermal crystallization solves the stability and regenerative problems of existing carbon materials in VOCs adsorption and removal, and achieves the VOCs treatment effect that is efficient adsorption and easy to regenerate.
Patent Information
- Application Number
- CN202311353298.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-18
AI Technical Summary
In the adsorption and removal of VOCs, existing carbon materials have problems such as poor thermal stability, flammable and explosive, difficulty in regeneration, easy blockage of pores, poor hydrophobicity and selectivity, which limits their practical application in industry.
Silicon-containing materials with multi-stage pore structures were prepared by hydrothermal crystallization method, and silicon sources, aluminum sources, sugar substances, nitrogen-containing compounds, alkali sources and dispersants were used as raw materials to control the proportion of raw materials and hydrothermal crystallization conditions to obtain materials that efficiently adsorb VOCs.
The prepared silicon-containing material has high VOC adsorption capacity, good analytical performance and easy regeneration. It has a simple preparation process and easy raw materials to obtain, which is suitable for industrial promotion.
Smart Images

Figure CN119838557A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of volatile organic compound treatment, and in particular to a silicon-containing material with VOC adsorption function, a preparation method and application thereof. Background Art
[0002] Volatile organic compounds (VOCs) are a general term for volatile organic compounds with a melting point below room temperature and a boiling point between 50-260°C, which are mainly derived from industrial production and transportation. According to the different chemical structures, VOCs can be divided into five categories: alkanes, alkenes, aromatic hydrocarbons, halogenated hydrocarbons and oxygen-containing organic matter. As one of the main factors in the formation of photochemical ozone and secondary organic aerosols, the emission of VOCs has great harm to human health and the ecological environment. As one of the common methods for VOCs treatment, adsorption has attracted widespread attention due to its low cost, high efficiency, and recyclability and reuse (ZhangX, GaoB, CreamerAE, et al.Journal of Hazardous Materials, 2017, 338, 102-123).
[0003] Although carbon materials such as activated carbon are currently widely used in the adsorption and removal of various VOCs due to their advantages such as large pore volume, simple operation and low price, carbon materials also have problems such as poor thermal stability and chemical stability, flammability and explosion, difficulty in regeneration, easy pore blockage, poor hydrophobicity and selectivity (Makowski W, Kus'trowski P. Microporous and Mesoporous Materials, 2007, 102 (1-3), 283-289), which seriously limit their practical application in industry.
[0004] Molecular sieves not only have a large specific surface area, but also have strong hydrophobic properties, good thermal stability and hydrothermal stability, are non-toxic and harmless to the environment, and have broad application prospects in the field of adsorption. Multi-level pore molecular sieves are molecular sieves composed of two or more different pore structures. While combining the characteristics of different pore structures, this structure can give full play to the synergistic effect of multiple pores. These advantages make multi-level pore molecular sieves have broad application prospects in the adsorption of VOCs. Therefore, it is of great significance to develop a method for preparing multi-level pore molecular sieves with a simple preparation process and environmental friendliness. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a silicon-containing material with VOC adsorption function and a preparation method and application thereof.
[0006] In order to achieve the above-mentioned purpose, the present invention provides, on the one hand, a method for preparing a silicon-containing material with VOC adsorption function, the preparation method comprising: hydrothermally crystallizing a crystallization raw material containing a silicon source, an optional aluminum source, an additive R1, an additive R2, an alkali source and a dispersant, wherein the weight ratio of the silicon source, R1 and R2 calculated as SiO2 is 1000:1-150:10-300, the additive R1 is at least one of sugar substances, and the additive R2 is at least one of nitrogen-containing compounds.
[0007] A second aspect of the present invention provides a silicon-containing material having a VOC adsorption function.
[0008] A third aspect of the present invention provides a method for treating VOCs, the method comprising: contacting the VOCs with the silicon-containing material as described above.
[0009] A fourth aspect of the present invention provides the use of the silicon-containing material as described above in the adsorption of VOCs.
[0010] Through the above technical scheme, the silicon-containing material of the present invention has a large VOC adsorption capacity, high analytical performance, easy regeneration (nitrogen purging), and a multi-level pore structure. In a preferred embodiment of the present invention, high temperature is used for calcination, so that the silicon-containing material has a molecular sieve structure and good thermal stability. In addition, the preparation process of the present invention is simple, the raw materials are easily available, and it is easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 is a scanning electron microscope photograph of a silicon-containing material obtained according to a preferred embodiment of the present invention.
[0012] Figure 2 This is an XRD spectrum of a silicon-containing material obtained according to a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0013] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0014] The present invention provides a method for preparing a silicon-containing material with a VOC adsorption function, characterized in that the preparation method comprises: hydrothermally crystallizing a crystallization raw material containing a silicon source, an optional aluminum source, an additive R1, an additive R2, an alkali source and a dispersant, wherein the weight ratio of the silicon source, R1 and R2 calculated as SiO2 is 1000:1-150:10-300, the additive R1 is at least one of sugar substances, and the additive R2 is at least one of nitrogen-containing compounds.
[0015] In the present invention, the aluminum source is a selectively contained substance (which can be used or not), and the weight ratio of the aluminum source calculated as Al2O3 to the silicon source calculated as SiO2 can be 0-600:1000, such as 5:1000, 15:1000, 20:1000, 25:1000, 30:1000, 35:1000, 50:1000, 100:1000, 200:1000, 300:1000, 400:1000, 500:1000, 600:1000 or any value or range between the above values.
[0016] In the present invention, the silicon source can be selected from the common substances in the art that can provide silicon element, for example, the silicon source can be selected from at least one of silicon oxide, silicic acid, silicate, silicate and siloxane. Preferably, the silicon source is selected from at least one of tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, hexamethyldisiloxane, methyl silicone oil and ethyl silicone oil.
[0017] In the present invention, the aluminum source can be selected from the common substances in the art that can provide aluminum elements, for example, the aluminum source can be selected from at least one of aluminum alkoxide, aluminum oxide, aluminum hydroxide, aluminum salt and aluminate. Preferably, the aluminum source is selected from at least one of aluminum isopropoxide, pseudo-boehmite (AlOOH·nH2O, n=0.08-0.62), anhydrous aluminum oxide (Al2O3), aluminum hydroxide, aluminum nitrate, aluminum chloride, aluminum sulfate and sodium aluminate.
[0018] In a preferred embodiment of the present invention, the weight ratio of the silicon source calculated as SiO2 to R1 is 1000:10-100, such as 1000:10, 1000:13, 1000:14, 1000:15, 1000:20, 1000:50, 1000:90, 1000:100 or any value or range therebetween.
[0019] In the present invention, the additive R1 is at least one of the common carbohydrate substances in the art, but preferably, the additive R1 is selected from at least one of monosaccharides. The monosaccharide can be aldose and / or ketose, and can be at least one of triose, tetrose, pentose, hexose and heptose. Common monosaccharides such as glyceraldehyde, erythrose, thulose, arabinose, ribose, xylose, lyxose, glucose, mannose, fructose, and galactose are all suitable for the present invention. More preferably, the additive R1 is selected from at least one of glucose, fructose and mannose.
[0020] In a preferred embodiment of the present invention, the weight ratio of the silicon source calculated as SiO2 to R2 is 1000:20-250, such as 1000:25, 1000:30, 1000:50, 1000:100, 1000:150, 1000:200, 1000:250 or any value or range between the above values.
[0021] In the present invention, the additive R2 is at least one of the common nitrogen-containing organic substances in the art, but preferably, the additive R2 is selected from at least one of the nitrogen-containing compounds with a nitrogen content of ≥30% by weight (more preferably 30-70% by weight). The additive R2 can be a nitrogen-containing organic substance or a nitrogen-containing inorganic substance. Preferably, the carbon content of the additive is ≤30% by weight, more preferably ≤28% by weight. More preferably, the additive R2 is selected from at least one of urea, melamine and ammonium nitrate.
[0022] According to a particularly preferred embodiment of the present invention, the weight ratio of R2 to R1 is 1-5, such as 1, 1.5, 1.8, 2, 2.2, 2.5, 3, 3.5, 4, 4.5, 5 or any value or range therebetween.
[0023] As described above, a silicon-containing material with better performance can be obtained by combining specific types of additives R1 and additives R2 in specific weight amounts.
[0024] In the present invention, OH - The weight ratio of the alkali source to the silicon source based on SiO2 can be less than or equal to 2.8, preferably 0.02-2.5, such as 0.02, 0.05, 0.1, 0.15, 0.17, 0.18, 0.2, 0.3, 0.5, 1, 1.5, 2, 2.5 or any value or range between the above values. The alkali source can be selected from substances that can be hydrolyzed to produce hydroxyl groups common in the art, preferably, the alkali source is selected from alkali metal hydroxides and / or ammonia, more preferably at least one of sodium hydroxide, potassium hydroxide and ammonia. In the present invention, ammonia is usually used in the form of ammonia water.
[0025] In the present invention, the amount of the dispersant used can be such that the weight ratio of the dispersant to the silicon source calculated as SiO2 is less than or equal to 20, preferably 5-15, such as 5, 8, 9, 10, 11, 12, 13, 14, 15 or any value or range between the above values. The dispersant can be a substance commonly used in the art that is conducive to uniform dispersion of the raw materials, but preferably, the dispersant is selected from at least one of small molecule alcohols, especially small molecule alcohols with 1-6 carbon atoms, especially monohydric alcohols with 1-6 carbon atoms, and more preferably at least one of methanol, ethanol, n-propanol and isopropanol.
[0026] In the present invention, the amount of water in the crystallization raw material can make the weight ratio of water to silicon source calculated as SiO2 be 30-200, such as 30, 40, 45, 50, 55, 60, 80, 100, 150, 200 or any value or range between the above values.
[0027] In a preferred embodiment of the present invention, the conditions for the hydrothermal crystallization include: a temperature of 70-200°C, preferably 90-180°C, and more preferably 110-130°C.
[0028] In a preferred embodiment of the present invention, the hydrothermal crystallization conditions further include: a time of 4-80 h, preferably 5-60 h, and more preferably 45-50 h.
[0029] In the present invention, preferably, the method may further include aging the crystallization raw material before hydrothermal crystallization. The aging may be performed at room temperature and pressure, preferably, the aging conditions include: a temperature of 15-40°C (room temperature), a time of 5-24h, more preferably 11-13h.
[0030] In the present invention, in order to obtain a stable silicon-containing material, the method may further include sequentially drying and calcining the hydrothermal crystallization product after the hydrothermal crystallization.
[0031] More preferably, the drying conditions include: a temperature of 90-120° C. and a time of 10-36 h.
[0032] More preferably, the calcination conditions include: a temperature of 400-600° C., and more preferably 540-560° C. More preferably, the calcination conditions also include: a time of 3-10 h, and more preferably 5-7 h.
[0033] The present invention also provides a silicon-containing material having a VOC adsorption function, characterized in that the silicon-containing material is prepared by the preparation method described above;
[0034] Alternatively, the silicon-containing material includes Si and optionally Al, the weight ratio of Si calculated as SiO2 to Al calculated as Al2O3 is 0-600 (such as 20, 30, 40, 50, 60, 70, 80, 100, 200, 300, 400, 500, 600 or any value or range therebetween), and the XRD spectrum of the silicon-containing material has characteristic peaks of an MFI structure.
[0035] In the silicon-containing material of the present invention, Si and Al exist in the form of oxides.
[0036] Preferably, the silicon-containing material of the present invention is in a honeycomb shape and has a multi-level pore structure.
[0037] Preferably, the mesoporous specific surface area of the silicon-containing material of the present invention is 350-600m 2 / g, more preferably 500-550m 2 / g.
[0038] Preferably, the total pore volume of the silicon-containing material of the present invention is 0.1-0.5 cm 3 / g, more preferably 0.4-0.5cm 3 / g.
[0039] Preferably, the mesopore volume of the silicon-containing material of the present invention is 0.08-0.35 cm 3 / g, more preferably 0.25-0.33cm 3 / g.
[0040] Preferably, the average pore diameter of the silicon-containing material of the present invention is 2-8.5 nm, more preferably 5-7 nm.
[0041] The present invention also provides a method for treating VOC, characterized in that the method comprises: contacting VOC with the silicon-containing material as described above.
[0042] In the present invention, there is no special requirement for the amount of the silicon-containing material. The VOC adsorption capacity of every 100g of the silicon-containing material is ≥ 10g of VOC. Accordingly, when using the silicon-containing material to treat VOC, those skilled in the art can determine the amount of the silicon-containing material according to the adsorption capacity. Generally, the amount of the silicon-containing material can be 2-20g per gram of VOC.
[0043] In the present invention, the volatile organic compounds (VOCs) may include various common volatile organic compounds, including alkanes, olefins, aromatic hydrocarbons (such as benzene, toluene, ethylbenzene, n-propylbenzene, isopropylbenzene, etc.), halogenated hydrocarbons and oxygen-containing organic compounds.
[0044] In the present invention, there is no particular requirement for the contacting conditions, and the contacting can be carried out at normal temperature and pressure.
[0045] The present invention also provides the use of the silicon-containing material as described above in adsorbing VOC.
[0046] The present invention will be described in detail below by way of examples. In the following examples or comparative examples, the room temperature is about "25°C".
[0047] Example 1
[0048] 0.4 g of sodium aluminate, sodium hydroxide, glucose, urea, water and ethanol were mixed evenly, and tetramethyl orthosilicate was added. The prepared material was stirred at room temperature for 4 hours and aged for 12 hours. The aged material was placed in a crystallization kettle with a polytetrafluoroethylene liner and crystallized at 120° C. for 48 hours.
[0049] The weight of each raw material is as follows: Al2O3 / SiO2=0.03; R1 / SiO2=0.014; R2 / SiO2=0.028; OH - / SiO2=0.17; ethanol / SiO2=11; H2O / SiO2=50, wherein R1 and R2 represent sugar and nitrogen-containing organic matter respectively.
[0050] The obtained crystallized product was washed with water, centrifuged, dried at 110°C for 24 h to obtain a solid sample, and then calcined at 550°C for 6 h.
[0051] Example 2
[0052] 0.5 g of aluminum hydroxide, sodium hydroxide, fructose, melamine, water and methanol were mixed evenly, and hexamethyldisiloxane was added. The prepared material was stirred at room temperature for 5 hours and aged for 6 hours. The aged material was placed in a crystallization kettle with a polytetrafluoroethylene liner and crystallized at 180°C for 4 hours.
[0053] The weight of each raw material is as follows: Al2O3 / SiO2=0.015; R1 / SiO2=0.05; R2 / SiO2=0.1; OH - / SiO2=0.5; ethanol / SiO2=15; H2O / SiO2=100, wherein R1 and R2 represent sugar and nitrogen-containing organic matter respectively.
[0054] The obtained crystallized product was washed with water, centrifuged, dried at 120°C for 25 h to obtain a solid sample, and then calcined at 500°C for 8 h.
[0055] Example 3
[0056] 1 g of aluminum isopropoxide, ammonia water, mannose, ammonium nitrate, water and ethanol were mixed evenly, and methyl silicone oil (purchased from Sinopharm) was added, and the prepared material was stirred at room temperature for 8 hours and aged for 20 hours; the aged material was placed in a crystallization kettle with a polytetrafluoroethylene liner and crystallized at 70°C for 80 hours;
[0057] The weight of each raw material is as follows: Al2O3 / SiO2=0.005; R1 / SiO2=0.1; R2 / SiO2=0.2; OH - / SiO2=2; ethanol / SiO2=10; H2O / SiO2=200, wherein R1 and R2 represent sugar and nitrogen-containing organic matter respectively.
[0058] The obtained crystallized product was washed with water, centrifuged, dried at 90°C for 36 h to obtain a solid sample, and then calcined at 450°C for 10 h.
[0059] Example 4
[0060] The material was prepared according to the method of Example 1, except that sugar was replaced by ethylene glycol.
[0061] Example 5
[0062] The material was prepared according to the method of Example 1, except that the nitrogen-containing organic matter was replaced by tetrapropylammonium hydroxide.
[0063] Example 6
[0064] The material was prepared according to the method of Example 1, except that the amount of sugar and nitrogen-containing organic matter used was such that R1 / SiO2=1:1000 and R2 / SiO2=300:1000.
[0065] Example 7
[0066] The material was prepared according to the method of Example 1, except that the amount of sodium aluminate added was 0.
[0067] Comparative Example 1
[0068] The material was prepared according to the method of Example 1, except that the amount of sugar and nitrogen-containing organic matter used was such that R1 / SiO2=10 and R2 / SiO2=4.
[0069] Comparative Example 2
[0070] The material was prepared according to the method of Example 1, except that the sugar was replaced by nitrogen-containing organic matter.
[0071] Comparative Example 3
[0072] The material was prepared according to the method of Example 1, except that the nitrogen-containing organic matter was replaced by sugar.
[0073] Comparative Example 4
[0074] The material was prepared according to the method of Example 1, except that the sugar was replaced by a triblock copolymer (polyoxyethylene-polyoxypropylene-polyoxyethylene, P123, CAS NO. 9003-11-6).
[0075] Comparative Example 5
[0076] The material was prepared according to the method of Example 1, except that the nitrogen-containing organic matter was replaced by glycerol phosphate.
[0077] Comparative Example 6
[0078] The material was prepared according to the method of Example 1, except that no sodium hydroxide was used.
[0079] Comparative Example 7
[0080] The material was prepared according to the method of Example 1, except that ethanol was not used.
[0081] Test Example 1
[0082] The morphology and structure of the materials obtained in the above examples and comparative examples were analyzed and characterized, and the results are shown in Table 1.
[0083] Elemental analysis (X-ray fluorescence method, refer to GB / T 30905-2014) showed that the weight ratios of Si calculated as SiO2 to Al calculated as Al2O3 of the materials obtained in Examples 1-3 were 45, 80, and 230, respectively.
[0084] The morphology of the material was observed by a scanning electron microscope (SEM, model S-4800 field emission scanning electron microscope) and the XRD pattern of the material was measured by an X'Pert PRO X-ray diffractometer; the mesoporous specific surface area, total pore volume, mesoporous pore volume and average pore diameter of the material were measured by N2 adsorption / desorption curve; the SEM photo of the material obtained in Example 1 is shown in Figure 1 As shown, from Figure 1 It can be seen that the silicon-containing material of the present invention has a multi-level pore structure. Although not shown, the SEM photos of other embodiments are similar to Figure 1 Similar, both show a multi-level pore structure; the XRD spectrum of the material obtained in Example 1 is as follows Figure 2 As shown, from Figure 2 Characteristic peaks at diffraction angles 2θ=7.9°, 8.8°, 23.2°, and 24° can be observed, which are attributed to the characteristic peaks of the MFI type zeolite structure; although not shown, the XRD test results of other embodiments are similar to those of Figure 1 Similarly, it is shown that the silicon-containing material prepared in the present invention has an MFI structure.
[0085] Table 1
[0086]
[0087] Test Example 2
[0088] The materials obtained in the above embodiments and comparative examples are used for VOC adsorption. The specific steps are as follows: a gas containing VOCs with a volume concentration of 1000ppm (the main component is toluene) is passed into an adsorption tank containing a silicon-containing material. When the VOCs concentration at the outlet of the adsorption tank is equivalent to that at the inlet, ventilation is stopped, and the weight difference before and after the adsorption of the silicon-containing material is measured. The analysis of the adsorbent is to purge the silicon-containing material adsorbed with the adsorbed gas with 100ml / min of nitrogen at room temperature and pressure for 2h, and measure the weight of the silicon-containing material after purging. The regeneration of the adsorbent is to pass the VOCs gas into the silicon-containing material after nitrogen purge again. When the VOCs concentration at the outlet of the adsorption tank is equivalent to that at the inlet, ventilation is stopped, and the weight difference before and after the adsorption of the silicon-containing material is measured. The calculation formula for the adsorption amount is as follows:
[0089] Adsorption amount = weight difference before and after adsorption / loading weight of silicon-containing material × 100%
[0090] Analysis = Weight difference of adsorbent before and after purging / Weight difference before and after adsorption × 100%
[0091] Regeneration = weight difference before and after re-adsorption / loading weight of silicon-containing material × 100%
[0092] The results are shown in Table 2.
[0093] Table 2
[0094]
[0095]
[0096] It can be seen from the above results that the material obtained by using the example of the preferred embodiment of the present invention has a significantly better effect in adsorbing VOC.
[0097] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a silicon-containing material with VOC adsorption function, characterized in that: The preparation method comprises: hydrothermally crystallizing a crystallization raw material containing a silicon source, an optional aluminum source, an additive R1, an additive R2, an alkali source and a dispersant, wherein the weight ratio of the silicon source, R1 and R2 calculated as SiO2 is 1000:1-150:10-300, the additive R1 is at least one of sugar substances, and the additive R2 is at least one of nitrogen-containing compounds.
2. The preparation method according to claim 1, wherein The weight ratio of the silicon source calculated as SiO2, the aluminum source calculated as Al2O3, R1 and R2 is 1000:0-600:10-100:20-250; And / or, the weight ratio of R2 to R1 is 1-5.
3. The preparation method according to claim 1 or 2, wherein The silicon source is selected from at least one of silicon oxide, silicic acid, silicate, silicate ester and siloxane; and / or, the aluminum source is selected from at least one of aluminum alkoxide, aluminum oxide, aluminum hydroxide, aluminum salt and aluminate; and / or, the additive R1 is at least one selected from monosaccharides; And / or, the additive R2 is selected from at least one nitrogen-containing compound having a nitrogen content of ≥30 wt%.
4. The preparation method according to claim 3, wherein The silicon source is selected from at least one of tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, hexamethyldisiloxane, methyl silicone oil and ethyl silicone oil; And / or, the aluminum source is selected from at least one of aluminum isopropoxide, pseudo-boehmite, anhydrous aluminum oxide, aluminum hydroxide, aluminum nitrate, aluminum chloride, aluminum sulfate and sodium aluminate; and / or, the additive R1 is selected from at least one of glucose, fructose and mannose; And / or, the additive R2 is selected from at least one of urea, melamine and ammonium nitrate.
5. The preparation method according to claim 1 or 2, wherein: OH - The weight ratio of the alkali source calculated as alkali to the silicon source calculated as SiO2 is less than or equal to 2.8, preferably 0.02-2.5; Preferably, the alkali source is selected from alkali metal hydroxides and / or ammonia, more preferably at least one of sodium hydroxide, potassium hydroxide and ammonia.
6. The preparation method according to claim 1 or 2, wherein: The amount of the dispersant is such that the weight ratio of the dispersant to the silicon source calculated as SiO2 is less than or equal to 20, preferably 5-15; Preferably, the dispersant is selected from at least one of small molecule alcohols, more preferably at least one of methanol, ethanol, n-propanol and isopropanol.
7. The preparation method according to claim 1 or 2, wherein: The amount of water used in the crystallization raw material is such that the weight ratio of water to silicon source calculated as SiO2 is 30-200.
8. The preparation method according to claim 1 or 2, wherein: The conditions of the hydrothermal crystallization include: temperature of 70-200°C and time of 4-80h; Preferably, the conditions of the hydrothermal crystallization include: temperature of 90-180°C and time of 5-60h; Preferably, the method further comprises aging the crystallization raw material before hydrothermal crystallization, and the aging conditions include: temperature of 15-40° C. and time of 5-24 h.
9. The preparation method according to claim 1 or 2, wherein: The method further comprises drying and calcining the hydrothermal crystallization product in sequence after the hydrothermal crystallization.
10. The preparation method according to claim 1 or 2, wherein: The drying conditions include: temperature of 90-120°C and time of 10-36h; And / or, the calcination conditions include: temperature of 400-600° C. and time of 3-10 h.
11. A silicon-containing material having VOC adsorption function, characterized in that: The silicon-containing material is prepared by the preparation method described in any one of claims 1 to 10; Alternatively, the silicon-containing material comprises Si and optionally Al, the weight ratio of Si calculated as SiO2 to Al calculated as Al2O3 is 0-600, and the XRD spectrum of the silicon-containing material has characteristic peaks of MFI structure.
12. The silicon-containing material according to claim 11, wherein Si and Al exist in the form of oxides; and / or, the silicon-containing material is in a honeycomb shape; And / or, the mesoporous specific surface area of the silicon-containing material is 350-600m 2 / g; And / or, the total pore volume of the silicon-containing material is 0.1-0.5 cm 3 / g; And / or, the mesopore volume of the silicon-containing material is 0.08-0.35cm 3 / g; And / or, the average pore size of the silicon-containing material is 2-8.5 nm.
13. A method for treating VOC, characterized in that: The method comprises: contacting VOC with the silicon-containing material of claim 11 or 12.
14. The method according to claim 13, wherein: The amount of the silicon-containing material used is 2-20 g per gram of VOC.
15. Use of the silicon-containing material according to claim 11 or 12 in adsorbing VOC.
Citation Information
Patent Citations
Molecular sieve adsorbent for VOCs removal and preparation method thereof
CN110294483A
High-silicon ZSM-5 molecular sieve for adsorbing VOCs and preparation method and application thereof
CN112299443A
Method for preparing ZSM-22 molecular sieve
CN112537775A
Preparation method of ultrahigh-hydrophobicity VOCs adsorbent molecular sieve
CN112892471A
ZSM-5 molecular sieve as well as preparation method and application thereof
CN115991487A